Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Tekanan Darah Ibu Hamil dengan Hipertensi di Wilayah Kerja Puskesmas Sukarejo - Kusmaryati, Pauline; Murtiyarini, Ika; Astuti, Anastia (NHM PRESS, 2024)
Treatment of hypertension in pregnant women using non-pharmacological methods has begun to be widely used to reduce morbidity levels, including using deep breathing relaxation techniques. Breathing exercises can reduce stress hormones. This study aims to determine the effect of deep breathing relaxation techniques on the blood pressure of pregnant women with hypertension in the Sukarejo Community Health Center working area. This research is a quantitative research with the design used in this research being pre-experimental, in the form of a one group pretest and posttest design which was carried out in the Sukarejo Community Health Center Work Area in November 2022 – June 2023 involving 23 pregnant women with criteria such as being willing to be respondents , pregnant women with blood pressure > 140/90 mmHg. In this study, a t-test was used with the help of a computerized program with a significance level of α=0.05 or 5%. The results of the study showed that the results of the analysis of systolic blood pressure data before and after the breath relaxation technique was carried out, it was found that the p value was 0.000, indicating that there was a significant influence between the breath relaxation technique on reducing the systolic blood pressure of pregnant women with hypertension. The results of the analysis of diastolic blood pressure data before and after the breath relaxation technique was carried out showed a p value of 0.000, indicating that there was a significant influence between the breath relaxation technique on reducing the diastolic blood pressure of pregnant women with hypertension.